A Competency Model for a Specialist in Medical and Psychological Work in the Field of Road Safety - Bedina, I.A.; Burtsev, A.A.; Kochetova, T.V. (Psihologo-pedagogičeskie issledovaniâ, 2021)
This article is aimed at highlighting the problem of training practicing psychologists for medical and psychological work on the prevention, prevention of accidents and road traffic accidents, as well as a system for assessing suitability for driving a vehicle in the Russian Federation. The analysis of international experience in the development of educational and professional standards within the framework of the model of medical and psychological support for safe mobility is presented. The content of the activities of specialists in the field of traffic psychology is considered, the role of interaction with specialists in the field of transport medicine and transport pedagogy is emphasized. The issues related to the problem of replicating foreign models of training specialists in the field of road safety for modern Russian realities are touched upon. The results of the initial stage of development of the competence model of specialists (based on the Federal State Educational Standard) in the direction of preparation 44.04.02 "Psychological and pedagogical education" of the master's program "Traffic Psychology" are presented. Настоящая статья направлена на освещение проблемы подготовки психологов-практиков для медико-психологической работы по профилактике, превенции аварий и дорожно-транспортных происшествий, а также системы оценки пригодности к управлению транспортным средством в Российской Федерации. Представлен анализ международного опыта разработки образовательных и профессиональных стандартов в рамках модели медико-психологической поддержки безопасной мобильности. Рассматривается содержание деятельности специалистов в области психологии дорожного движения, подчеркивается роль взаимодействия со специалистами в области транспортной медицины и транспортной педагогики. Затронуты вопросы, связанные с проблемой репликации зарубежных моделей подготовки психологов в сфере дорожной безопасности для современных российских условий. Представлены результаты начального этапа разработки компетентностной модели специалистов (на основе ФГОС) по направлению подготовки 44.04.02 «Психолого-педагогическое образование» магистерской программы «Психология дорожного движения».